Sludge Reduction in the Activated Sludge Process Strengthened by Enhanced Ozonation Oxidation: Chen et al. (1st August 2017) - Chen, Yingwen; Zhang, Wei; Feng, Yangyang; Huang, Qiong; Shen, Shubao
ABSTRACT: : A novel radial‐axial mixer and microbubble ozone reactor for enhancing sludge disintegration was designed. In the batch studies, the new reactor was shown to be significantly effective in improving sludge disintegration and increasing ozone utilization. For ozone dosages of 0.02 to 0.3 gO3 /gTSS (total suspended solids) at pH = 10, the average sludge disintegration ratio was more than 17 ± 0.83% higher than that of the conventional reactor. An activated sludge process coupled with discharged sludge ozonated was run for 60 days to evaluate the influence of ozonated sludge feeding on the sludge yield coefficient and effluent quality. Although the effluent chemical oxygen demand (COD) and suspended solids (SS) increased slightly, these values were well below the discharge limit. Furthermore, a sludge reduction efficiency of 95% was attained. The experimental results indicated that the combination of sludge ozonation with the activated sludge process could generate a high quality of effluent and a small sludge yield.